Persuasion. - Austen, Jane (Open Road Media Romance, 2015)
Jane Austen's classic novel about a second chance at love Anne Elliot is a perfect catch. Born to a landed family, she's observant and intelligent. When Anne came of age, she accepted a proposal from the ambitious officer Frederick Wentworth. Unfortunately, Wentworth's modest means made him a poor choice for the Elliot family, and Anne was persuaded to call off the engagement. One refused marriage and nearly a decade later, Anne has not forgotten about Wentworth. Little does she know that her fortune is about to change. When the Elliots make ill-advised investments and lose their money, they are forced to rent out their ancestral home and move to Bath. There, Anne once again meets Wentworth, who is now a captain, in what could be her second and final chance at love and marriage. Buttressed by the author's humane characterization and sharp social commentary, Persuasion is a must-read for any Jane Austen fan. This ebook has been professionally proofread to ensure accuracy and readability on all devices.